PERAN KOMITMEN ORGANISASIONAL MEMEDIASI PENGARUH KEPUASAN KERJA TERHADAP TURNOVER INTENTION - Kartika Candra, Putu Dodik; Riana, I Gede (E-Jurnal Manajemen, 2017)
The purpose of this study is to determine the role of organizational commitment mediate the effect of job satisfaction on turnover intention. Sample in this research is 92 employee determined by using probability sampling method. Data collection was done by distributing questionnaires. Analysis technique used is descriptive analysis and path (path) , while to test the role of mediation techniques used analysis of analysis techniques sobel. Result of the analysis shows that job satisfaction and organizational commitment have positive and significant  to intention turnover employe. Organizational commitment is significantly able to mediate the effect of job satisfaction on turnover intention. This shows that if organizational commitment is high then employee job satisfaction is assured to be high too and thus their desire to get out of company is lower. Research on hotel blue point shows high level of employee job satisfaction so that this also result to decreasing of turnover intention level.                                              Keywords: organizational commitment, job satisfaction, turnover intention